Implementation of Recording System Regular Spending Cost Based Software Online Accounting For Record Expenditures on the Company - Manurung, Edward Boris P; Ariessanti, Hani Dewi; Desrianti, Dewi Immaniar (Pandawan, 2017)
n the finances of a company, to record any costs incurred by the company, such as promotional costs, advertising, water, electricity and others is certainly very important as evidence for the leadership of the company in taking a decision. And on this web-based online accounting system, there are cost facilities where the expenditure of each transaction can be recorded more effectively and efficiently. in this cost menu there are features such as making new fees to record new transaction costs incurred by the company. then at this cost facility can also be done to make the cost of spending using import facilities which can facilitate the accountant in recording the cost of expenditure without having to make costs one by one and facilitate the leadership of the company in monitoring the cost of corporate expenses. then on the cost menu also uses CRUD system (Create, Read, Update, and Delete) which can be done to change the cost that has been made before due to wrong set transaction date and other errors. Can remove expenses that have been paid or paid off of course. By using Online Accounting Software will minimize criminality on the company because it has been certified ISO / IEC 2700. And for important reports such as corporate expenses costs every month has been stored on the Cloud to facilitate the leadership of the company in monitoring financial reports in real-time. On this fee menu accountants can view, add, delete, or change customer data to the company, so it can facilitate in managing and convey information on monthly expenses on the company.